Peralihan Kewenangan dari Pemerintah Daerah ke Pemerintah Pusat dalam Pengawasan Pertambangan Batuan di Kali Noemuti Kabupaten Timor Tengah Utara - Antonia Konfat; Detji K. E. R. Nuban; Norani Asnawi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The enactment of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 on Mineral and Coal Mining has fundamentally restructured the distribution of governmental authority in Indonesia’s mining sector, particularly regarding the supervision of rock mining activities. This study aims to analyze the transfer of supervisory authority over rock mining from regional governments to the Central Government and to examine its legal implications for mining governance in Kali Noemuti, North Central Timor Regency. This research employed normative legal research using statutory and conceptual approaches. The legal materials consisted of primary, secondary, and tertiary legal sources analyzed through qualitative descriptive methods. The findings indicate that the transfer of authority reflects a policy of centralized governance intended to strengthen state control over mineral resources, standardize supervision, and enhance legal certainty in the mining sector. However, the centralization of supervisory authority has also shifted legal responsibility from regional governments to the Central Government, while limiting the operational role of local governments. The study further reveals that centralized supervision has not fully addressed environmental and social impacts resulting from mining activities, highlighting the need for stronger coordination between central and regional governments to ensure effective supervision, environmental protection, and sustainable mineral resource management.